The effect of gender, age and product type on the origin induced food product experience among young consumers in Finland - Kumpulainen T; Vainio A; Sandell M; Hopia A. (My University, 2022)
Locally produced and sourced food products are gaining popularity among consumers. The effect of the expectations induced by the origin of the food was studied with 1491 consumers in two separate studies among different age groups. In order to test the consumer response to the product origin neutral, domestic, and local conditions were used. Consumers evaluated the product's pleasantness, their probability to choose it, the overall quality, and their willingness to pay. To gather information on whether the phenomenon was consistent, independent from the product category, three different types of products were tested (meat, bread, and vegetables). Our results show that a closer origin does not necessarily produce a positive response, but that there are several moderating factors such as gender, age, and product type. Female university students responded equally to domestic and local origins in the case of bread, but for meat products, only those of local origin induced a positive reaction. In this study population, the male respondents only reacted to a local origin in the case of bread, while domestic meat products provided similar results to local origins. Among young men consumers in the 7th-9th grades responded to the local origin of vegetables positively, while others among the youngest consumers, the origin did not induce a significant effect. The results indicate that even when the product is not appealing itself, locality can still increase the perceived quality.